Orchard management practices affect arbuscular mycorrhizal fungal root colonisation of almond. Issue 4 (1st October 2020) - Vasilikiotis, Christos; Li, Meng; Schmidt, Jennifer E; Azimi, Anna; Garcia, Joshua; Volder, Astrid; Lampinen, Bruce; Gaudin, Amélie CM
ABSTRACT: Arbuscular mycorrhizal fungi (AMF) are mutualistic fungi that play important roles in plant nutrition and soil ecosystem functions. While AMF are known to benefit diverse host plants under a range of conditions, little is known about their presence in commercial almond orchards and how frequently used management practices regulate AMF root colonisation. A large-scale survey of almond orchards in the Central Valley of California was conducted to determine the extent of mycorrhizal associations with roots and the impact of orchard management practices and soil properties on AMF root colonisation rates. The roots in all orchards were colonised, with an overall average rate of 64.4%. Organically managed orchards had higher AMF root colonisation rates (73.2%) as compared with conventionally managed orchards (62.1%), primarily due to the presence of soil vegetative cover rather than organic matter inputs. Choice of rootstock and fumigation had only marginal effects while inoculation at planting increased AMF root colonisation of young trees by 27% compared to non-inoculated control. These results highlighted the ubiquitous presence of AMF in commercial almond orchards and significant interacting influences of common management practices on AMF root colonisation under field conditions. Further research into the functional implications of mycorrhizal associations in these orchards will help guide the development of management practices that increase AMF abundance and root colonisation to improve the sustainability of this rapidly expanding industry.